2022
DOI: 10.1038/s41467-022-30889-1
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary action of mutations reveals antimicrobial resistance genes in Escherichia coli

Abstract: Since antibiotic development lags, we search for potential drug targets through directed evolution experiments. A challenge is that many resistance genes hide in a noisy mutational background as mutator clones emerge in the adaptive population. Here, to overcome this noise, we quantify the impact of mutations through evolutionary action (EA). After sequencing ciprofloxacin or colistin resistance strains grown under different mutational regimes, we find that an elevated sum of the evolutionary action of mutatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 84 publications
0
13
0
Order By: Relevance
“…The different classes of antibiotics used in this study against S. enterica have been tested in earlier studies ( Geornaras and von Holy, 2001 ; Jones et al, 2002 ; Muhammad et al, 2010 ; Chang et al, 2021 ). Studies in E. coli have found that resistance against antibiotics changes over the course of ALE studies ( Maeda et al, 2020 ; Marciano et al, 2022 ). E. coli strains sensitive to carbapenem were found to develop resistance against carbapenems by the 15th generation in another ALE study ( Geng et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…The different classes of antibiotics used in this study against S. enterica have been tested in earlier studies ( Geornaras and von Holy, 2001 ; Jones et al, 2002 ; Muhammad et al, 2010 ; Chang et al, 2021 ). Studies in E. coli have found that resistance against antibiotics changes over the course of ALE studies ( Maeda et al, 2020 ; Marciano et al, 2022 ). E. coli strains sensitive to carbapenem were found to develop resistance against carbapenems by the 15th generation in another ALE study ( Geng et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Food-producing animals and their products have been identified as a source of resistance genes [ 23 ]. The resistance genes in E. coli are acquired through selective pressure, induction, or mutation [ 24 ]. Bacterial AMR genes can be spread horizontally and vertically to other bacteria, and they can also infiltrate the human food chain [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…The mechanism of antibiotics and drugs is not completely understood, particularly in the case of newly arising diseases [ 6 ]. Furthermore, with mutations and other changes, it makes it more difficult to understand these mechanisms [ 77 ]. Additionally, the resistance behavior changes from cell level to micro-organism community level.…”
Section: Ml/dl For Amr Prediction: Challenges and Towards Practical I...mentioning
confidence: 99%